Vocational Exploration in Middle School: Motivational Characteristics of Students and Perceptions of the Learning Climate - Duchesne, Stéphane; Mercier, Adéline; Ratelle, Catherine F. (Canadian Journal of Counselling and Psychotherapy, 2012)
<span lang="EN-US" style="line-height: 115%; font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> The goal of this study was twofold: first, to identify vocational exploration profiles in the second year of middle school (Grade 8), and second, to distinguish these profiles in terms of sociomotivational variables. The sample included 521 students (255 boys, 266 girls) attending middle schools in Quebec. Results revealed three vocational exploration profiles: high exploration, exploration through discussion, and low exploration. Students in the high exploration profile were distinguished by their perceptions of the classroom climate as performance-oriented, their personal achievement goals, and their personal motivations. Results are discussed in light of their implications for the vocational and motivational literature.